Ganglion cell complex and retinal nerve fiber layer thickness in gestational diabetes mellitus - Shadman Parveen; Kavita Bhatnagar; Pratibha Singh; Seema Meena; Suwarna Suman; Sakshi Shiromani (Taiwan Journal of Ophthalmology, 2022)
PURPOSE: The purpose of this study was to compare ganglion cell complex and peripapillary retinal nerve fiber layer (RNFL) thickness between pregnant females with gestational diabetes mellitus (GDM) and healthy pregnant females. MATERIALS AND METHODS: This was a single-center, prospective, analytical cross-sectional study including pregnant females with a gestational age of 24 weeks or more in the GDM and control groups. The GDM group included 162 pregnant females with GDM, and the control group included 162 healthy pregnant females. Peripapillary RNFL (pRNFL), macular RNFL (mRNFL), GCL+ (ganglion cell layer [GCL] + inner plexiform layer [IPL]), and GCL++ (mRNFL + GCL + IPL) thickness were analyzed using spectral-domain optical coherence tomography (OCT), and comparisons were made between the groups. RESULTS: Both the groups had similar mean age (P = 0.219), intraocular pressure (P = 0.186), central corneal thickness (P = 0.689), Schirmer test value (P = 0.931), and tear breakup time (P = 0.651). The mean pRNFL thickness of the GDM and control groups was 100.75 ± 8.36 μm and 106.77 ± 8.44 μm (P < 0.0001). pRNFL was significantly thinner in all four quadrants (P < 0.05) in the GDM compared to the control group. We observed that the mean mRNFL, GCL+, and GCL++ thickness were significantly reduced in GDM in comparison to the control group (P < 0.05). CONCLUSION: Our study showed that OCT plays an indispensable role in determining initial retinal changes caused by GDM before the development of diabetic retinopathy.